(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
In this research, we study the efforts of Abu Zaid Al-Ansari in his citation of the poetic witness of grammar in his book Anecdotes, trying to clarify the method of Abu Zaid in his martyrdom of poetry on grammatical rules to confirm his doctrine of grammar. What we wrote is cited as evidence, which is poetry within the time of protest, and what it implied in terms of attribution of evidence and disagreement in its narration and lineage.